Kakovost življenja po rekonstrukciji sprednje križne vezi - Hriberšek, Maja (Obzornik zdravstvene nege, 2021)
Introduction: Anterior cruciate ligament reconstruction is a well-established treatment method after anterior cruciate ligament rupture. It is important to evaluate the overall impact of the surgery on an individuals health, which can be reflected in the quality of life. The purpose of the study was to determine the quality of life of patients after anterior cruciate ligament reconstruction. Methods: An integrative literature review based on the PRISMA methodology was used. Articles from 2009 to 2019 were included. The literature search was performed in the PubMed, MEDLINE, CINAHL, ScienceDirect, Web of Science and COBISS databases. A content analysis of research findings was conducted. Results: Of the 1,141 identified hits, 21 were included in the final analysis. It has been found that questionnaires and scales can be used after anterior cruciate ligament reconstruction to evaluate two aspects: knee-related quality of life and health-related quality of life. The majority of studies reported on good quality of life. Better results are reported in measuring health-related quality of life. Several different factors can affect the results and outcomes of the quality of life after surgery. Discussion and conclusion: Anterior cruciate ligament reconstruction can affect the quality of life of patients. Research findings may help in preoperative patient education about short- and long-term outcomes after surgery and for developing strategies to improve the postoperative quality of life.
Keywords: kolenski sklep; pacienti; pooperativni izidi; rekonstrukcija; sprednja križna vez; vprašalniki